95Mo NMR study of the effect of structure on complexation of molybdate with alpha and beta hydroxy carboxylic acid ligands. (16th August 2016) - Yoder, Claude H.; Christie, Emily L.; Morford, Jennifer L.
Graphical abstract: The utility of the quadrupolar, spin 5/2 95 Mo nucleus in NMR studies of complexation of molybdate have been demonstrated using model alpha hydroxy carboxylic acids. The 95 Mo NMR spectra show a down field shift of the resonance upon complexation, presumably due to the smaller 1/Δ E paramagnetic shift term for the octahedral molybdate complexes relative to the tetrahedral molybdate ion. The 95 Mo resonances are sufficiently distinct to establish three solution complexes for the reaction of lactic acid with molybdate. The Lewis acidity of the negatively charged molybdate ion is rationalized with two schemes for the reaction with the chelating bidentate alpha hydroxy carboxylic acids. Abstract: The utility of the quadrupolar, spin 5/2 95 Mo nucleus in NMR studies of complexation of molybdate have been demonstrated using model alpha hydroxy carboxylic acids. The 95 Mo NMR spectra show a down field shift of the resonance upon complexation, presumably due to the smaller 1/Δ E paramagnetic shift term for the octahedral molybdate complexes relative to the tetrahedral molybdate ion. The 95 Mo resonances are sufficiently distinct to establish three solution complexes for the reaction of lactic acid with molybdate. The effect of the structure of hydroxy carboxylic acids on complexation to molybdate (MoO4 2− ) was studied with 13 C and 95 Mo NMR spectroscopy. The use of the NMR spectra of both nuclei allows monitoring of the Lewis acidic molybdate site and the Lewis basic ligands. The beta hydroxy carboxylic acids, 3-hydroxypropanoic acid and salicylic acid, did not form complexes with molybdate, suggesting a preference for 5-membered chelated rings. The Lewis acidity of the negatively charged molybdate ion is rationalized with two schemes for the reaction with the chelating bidentate alpha hydroxy carboxylic acids.